Struktur Histologis Hepar, Intestinum, dan Ren Burung Cerek Jawa (Charadrius javanicus Chasen 1938) Dengan Kontaminasi DDT di Delta Sungai Progo Yogyakarta - Dewi Puspita Sari; Suwarno Hadisusanto; Istriyati I (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2014)
Residues of DDT (Dichloro Diphenyl Trichloroethane) in the river environment can get into the Bird's body through an intermediary Javan Plover natural feed. Residues of DDT will experience biomagnification and biotransformation in the body organism. The purpose of this research was to determine residue of DDT in the Progo’s mudflat region, several organs of birds, and their impact on liver, intestine, and kidney Javan Plover. This research was located in Progo’s downstream. The method of environment and feed sampling done directly on site. The bird sampling using mist nets. Detection of residues DDT in environment samples by gas chromatography. Measurement of DDT residues in feed and organs of birds with spectrophotometer. Preparation of histological slide from liver, intestine, and kidney using paraffin method (with Hematoxilin & Eosin and Mallory Acid Fuchsin staining). Quantitative Data obtained from the measurement results of environment, feed,and organs of Javan Plover samples. Qualitative data analize by descriptively. The analysis showed DDT residues detected in area’s Progo downstream, natural feed and Javan plover’s organ. Analysis shows chronic effects posed by DDT residue on the histological structure of liver, intestine, and kidney of Javan Plover.Keywords: DDT (Dichloro Diphenyl trichloroethane), histological structure, Javan Plover(Charadrius Javanicus Chasen 1938), Progo’s River